Administrative Data Research Northern Ireland (ADR NI) - O'Reilly, Dermot; Bateson, Orla; McGreevy, Gemma; Snoddy, Chris; Power, Tracy (International Journal of Population Data Science, 2020)
Background The Administrative Data Research Northern Ireland (ADR NI), is a partnership between academia and the local statistics agency to advance the access to and use of administrative data in Northern Ireland. These goals are currently being advanced by undertaking a series of demonstrator Strategic Impact Projects developed to provide input to departmental areas of research interest and the current draft Programme for Government. Approach ADR NI does not currently operate as a data repository but will negotiate access to and link subsets of administrative data from other departments and agencies as required for specific and approved projects. It is, however, anticipated that this model will broaden with the creation and retention of large linked datasets that could be used to address questions across a range of policy areas. At present accredited researchers can access the anonymised data only from within the safe setting situated in Belfast, although consideration is being given to using the Office for National Statistics Secure Researcher Service to access data more widely within the UK. ADR NI is currently being used to inform policy in a wide array of areas including health, education, environmental and urban planning. Discussion ADR NI continues to develop and change. The growing confidence amongst data owners which has been supported by new and facilitating UK legislation has increased the willingness and ability to share and link administrative data. However, the associated logistical and administrative processes for accessing data will need further streamlining so that the timelines become more efficient and predictable. The evidence for the potential utility of research based on administrative data to influence policy continues to grow. Conclusion Over the last decade we have demonstrated to data owners and the different publics that it is safe and acceptable to link administrative data for public benefit. The evolution and maturation of the ADR NI progresses apace and we continue to learn from developments in our sister organisations throughout the UK and throughout the world. We look forward to greater access to and use of administrative data both within Northern Ireland and across the UK.